A prática como componente curricular: um estudo em cursos de licenciatura em matemática - Perentelli, Léia Fernandes (2008)
The purpose of this research was to study the Mathematics Licensure Courses in two Great São Paulo Institutes of Higher Education, one university and one sole College. The intention of the study is to answer the following research question: How is practice being put into part of the curriculum load in the Licensure Course in Mathematics? In the bibliographic survey done in the Didactics and Teaching Practice National Meeting, it was possible to grasp few innovative experiences that would fit the ongoing legislation. Semistructured interviews were done with two of the course coordinators and with four professors of Teaching Practice, with the purpose of understanding how the 400 Practice hours as a part of the curriculum load are being put into the teaching projects and verifying how they are being understood by those who work with them. The researches done by Candau (1987) and Ludke (1997) had already pointed out the difficulties regarding the changes in the profile and structure of the Licensure program, in the magistrate as a profession and in the organization of the school work. It was observed in the two Institutes of Higher Education that, in their intentions to put Practice into a part of the curriculum, there is an attempt to restructure the curriculum load in a way to adapt them to the current guidelines. The university has put part of the Practice hours into nonattendance activities and the College has distributed a part of the hours to all other disciplines of the curricular load, under the responsibility of the professor managing the Teaching Practice discipline. One difficulty noticed by the teachers who were interviewed is relative to the assessment of these non-attendance and activities proposed, which the student does not take part and does not get involved in the same way as in the attendance activities. Both institutions are seen by the researchers as making an effort to diminish the existent divergences and to search for coherence between what is written in the teaching project and what really happens in the performance of the professor responsible in classroom